TANTANGAN IMPLEMENTASI PEMBELAJARAN CODING DALAM PENGUATAN KEMAMPUAN NUMERASI - Tri Rahmawati Fazrin; Deri Hendriyawan; Akhmad.E.Firlli Dimyati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Pursuant to Law No.59 of 2024, the government has prioritized the cultivation of superior, globally competitive human capital to navigate the complexities of Industry 4.0 and Society Era 5.0. To align with these strategic imperatives, the integration of coding and Artificial Intelligence (AI) into the educational curriculum will commence in the 2025-2026 academic year. However, the translation of this policy into practice encounters significant multifaceted obstacles. Employing a scoping review methodology, this study delineates the critical barriers to implementing coding instruction as a mechanism for strengthening numeracy in elementary schools, Identified challenges include the pedagogical preparedness of educators, systemic deficits in infrastructure and technological acces, and variance in student aptitude. It is paramount that these impediments be mitigated to ensure coding instruction effectively catalyzes the enhancement of student numeracy.